The Hungry Ant: Development of Video-Based Learning on Polyhedron - Hermita, Neni; Putra, Zetra Hainul; Alim, Jesi Alexander; Tang, Jianlan; Wijaya, Tommy Tanu; Li, Li; Pereira, Jerito; Tamur, Maximus (International journal of interactive mobile technologies, 2021)
This research on learning media development is to answer the challenge of using technology in this 21st century wherein technology is growing rapidly. The purpose of this research is to develop a learning media in the form of learning video on primary school topics. Researchers chose polyhedron to be the research subject. This search will use the 4D model and will only focus from the define up to the development stage. While the small-scale try-out and disseminate of the learning video can be done in another research. According to the validation result, the hungry ant video passed the validation and only needed a few revisions. The hungry ant video would be able to help students to visualize the shape of polyhedron, finding the diagonal space, proofing the area and volume formulas. Future research can analyze effect of the hungry ant video towards the students’ critical thinking ability.